2017
DOI: 10.21608/jesr.2017.57420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa Oleifera Leaf Extract on Growth, Metabolites and Antioxidant System of Barley Plants

Abstract: oringa oleifera is an important and promising tree, growing in many arid and semi-arid areas. Moringa plant is effective and suitable source of nutrition and medication. The present work was carried out to study the response of two barley genotypes to a foliar application of moringa leaf extract (MLE) as a growth enhancer at the vegetative stage. The obtained result showed enhanced antioxidants activities (superoxide dismutase, peroxidase & catalase) in leaves of the barley genotypes under MLE application comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, Rosa hybrida plants subjected to the treatment with 6-benzyleaminopurine (BAP) showed significant upregulation in the antioxidant enzymes and downregulation in malondialdehyde activity and relative conductivity (Wang et al, 2022). Moringa oleifera is a famous tree known for the antioxidant properties of its leaf extracts (MLE) (Ahmed, 2016). It also comprises various plant growth regulators, such as cytokinins (Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Rosa hybrida plants subjected to the treatment with 6-benzyleaminopurine (BAP) showed significant upregulation in the antioxidant enzymes and downregulation in malondialdehyde activity and relative conductivity (Wang et al, 2022). Moringa oleifera is a famous tree known for the antioxidant properties of its leaf extracts (MLE) (Ahmed, 2016). It also comprises various plant growth regulators, such as cytokinins (Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the productivity and growth of many plants grown in normal conditions, this kind of natural biostimulant has been applied as a foliar application [21][22][23]. To our knowledge, few smallscale experiments have been conducted to investigate the effect of moringa mlant extract on barely crops for productivity [24]. At field scale, no study has been reported using a combined application of moringa (leaf, root, and seed) extract.…”
Section: Introductionmentioning
confidence: 99%